First record of the rare deep-sea polychaete Rhamphobrachium (Rhamphobrachium) agassizii (Annelida: Onuphidae) in European waters. (24th August 2020) - Arias, Andrés; Paxton, Hannelore
Abstract: Rhamphobrachium ( Rhamphobrachium ) agassizii is reported from the Cantabrian Sea, Spain, from depths of 925–1207 m. This is its first record off the Iberian Peninsula and in European waters, representing its northernmost distribution in the North Atlantic Ocean to date. Previous reports of R. ( R. ) agassizii from the eastern and western North Atlantic demonstrate its apparent amphi-Atlantic distribution, which appears consistent with the distribution of the main Atlantic currents. It is a typical deep-water species with its deepest record at 2165 m from the Azores archipelago. The specimens were collected singly at two stations, attesting to the rarity of the species in contrast to its congener R. ( Spinigerium ) brevibrachiatum which was the most dominant polychaete species in a previous study.